ANTI-TUBERCULOSIS DRUG RESISTANCE IN PREVIOUSLY UNTREATED PULMONARY TUBERCULOSIS PATIENTS IN PUNE, INDIA - MICHAEL PEREIRA,; DINESH SHETA,; SHIVAHARI V. GHORPADE,; SANJAY N. GAIKWAD,; RAHUL M. LOKHANDE,; SRIKANTH P. TRIPATHY,; SANJAY M. MEHENDALE,; ARUN R. RISBUD, (International Journal of Pharma and Bio Sciences, 2013)
Emergence of multidrug-resistant tuberculosis (MDR-TB) has been a cause of concern in both developed and developing countries. Hence, there is a need for continuous monitoring of drug resistance to anti-tuberculosis drugs in tuberculosis patients. A study was conducted to determine the prevalence anti-TB drug resistance in Mycobacterium tuberculosis isolates obtained from sputum samples of clinically suspected TB patients with no history of previous anti-TB treatment attending a tertiary care hospital from February 2006 to August 2007 in Pune, India. Mycobacterium tuberculosis isolates were subjected to drug susceptibility testing (DST) to four firstline anti-TB drugs namely Isoniazid, Rifampicin, Streptomycin and Ethambutol by Bactec MGIT 960 system being currently used in the Revised National Tuberculosis Control Program (RNTCP). It was found that MDR-TB prevalence in newly diagnosed pulmonary tuberculosis patients in Pune has not increased compared to the earlier data. Adequate data on MDR-TB at national and regional level are not available. Hence, it is essential to conduct nationwide drug resistance surveillance for TB with continuous monitoring of trends to curb the emergence of drug resistance to ensure the success of tuberculosis control programs in the country.